California Bearing Ratio (CBR) improvement of Kuantan clay subgrade by using high density polyethylene (HDPE) as stabilizer - Mohd Zulfadli, Juhari (2012)
Nowadays, the application of usmg high density polyethylene (HDPE) especially for storage and marketing of many liquids product are increased day by day. The design of these containers is usually for spot use with short life span and the consumer will discard them after used because of those we have to promote the utilizing of HDPE as polluted material as in road construction. The expecting municipal waste production in Malaysia will increase up to 300,000 tons near to 2020 which is from the human life. By this fact, the waste material from HDPE product such as plastic container also will be increase. That polluted waste can be as additives material in soil stabilization for road construction in Kuantan clay subgrade. This study proposed an assessment of the utilization of HDPE fibers as stabilizer of clay subgrade. The research will be conducted several of contents of HDPE fibers from waste plastic mixed with Kuantan clay as a samples. A series of California Bearing Ratio (CBR) test will carry out to the soil samples to estimates the optimum mixture design. The samples will set up by mixing soil samples with several of HDPE fibers and at optimum water content. By depending engineering properties of soils, it will stabilize the soft sub grade. The amount of HDPE tried were 3%, 6% and 9% by total weight. The proposed technique can be used to advantage in. ground improvement and modification for highway project also in embankment project.